CpG and UpA dinucleotides in both coding and non-coding regions of echovirus 7 inhibit replication initiation post-entry - Fros, Jelke Jan; Dietrich, Isabelle; Alshaikhahmed, Kinda; Passchier, Tim Casper; Evans, David John; Simmonds, Peter (eLife, 2017)
Most vertebrate and plant RNA and small DNA viruses suppress genomic CpG and UpA dinucleotide frequencies, apparently mimicking host mRNA composition. Artificially increasing CpG/UpA dinucleotides attenuates viruses through an entirely unknown mechanism. Using the echovirus 7 (E7) model in several cell types, we show that the restriction in E7 replication in mutants with increased CpG/UpA dinucleotides occurred immediately after viral entry, with incoming virions failing to form replication complexes. Sequences of CpG/UpA-high virus stocks showed no evidence of increased mutational errors that would render them replication defective, these viral RNAs were not differentially sequestered in cytoplasmic stress granules nor did they induce a systemic antiviral state. Importantly, restriction was not mediated through effects on translation efficiency since replicons with high CpG/UpA sequences inserted into a non-coding region were similarly replication defective. Host-cells thus possess intrinsic defence pathways that prevent replication of viruses with increased CpG/UpA frequencies independently of codon usage. Living things store their genetic material as molecules of DNA or a related chemical called RNA. Both DNA and RNA contain building blocks known as bases. There are several different types of bases and the specific order they appear in a DNA or RNA molecule encodes the genetic information. In RNA these bases are known as cytosine, guanine, adenine and uracil (or C, G, A and U for short). The order that bases appear in DNA and RNA can be highly biased. For example, in RNAs from animals with backbones (also known as vertebrates), cytosine followed by guanine and uracil followed by adenine occur less often than mathematics would predict. Viruses are particles that contain DNA or RNA surrounded by a coat made of proteins. They are unable to multiply by themselves and must therefore invade the cells of host organisms. Viruses that infect vertebrates mimic the base biases found in their host, a strategy that likely helps the virus’ genetic material to hide within host cells. Previous experiments have shown that viruses engineered to have more cytosines followed by guanines and uracils followed by adenines were easier to eliminate. However, it is not clear how this worked. Fros et al. investigated the ability of a virus called echovirus 7 to multiply inside the cells of humans and several other vertebrates. The experiments show that artificially increasing the number of cytosines followed by guanines and uracils followed by adenines in this virus reduced the ability of the virus to multiply immediately after the virus had entered the host cell. The location of the changes did not have any effect on how strongly the virus was inhibited. Furthermore, Fros et al. confirmed that these changes did not affect the ability of the virus’ genetic material to make the proteins it needs to multiply and make its coat. This suggests that the host specifically prevents the virus genetic material from being copied, solely based on the order of the bases in the viral genetic material. These findings provide evidence that human and other vertebrate cells contain factors that recognize and rapidly respond to foreign genetic material with biases in their genetic code that do not match their own. In the future, artificially increasing the frequency of specific orders of bases in viral genomes could be used to design more effective vaccines against diseases caused by viruses.